Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Explore our Q&A platform to find in-depth answers from a wide range of experts in different fields. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
A mathematical proof can be carried out by mathematical induction and by contradiction
How to prove by induction
The function is given as:
[tex]d(n) = \frac{n(n + 1)}{2}[/tex]
When n = 1, we have:
[tex]d(1) = \frac{1(1 + 1)}{2}[/tex]
[tex]d(1) = 2[/tex]
When n = k, the function becomes
[tex]d(k) = \frac{k(k + 1)}{2}[/tex]
When n = k + 1, the function becomes
[tex]d(k) + k + 1 = \frac{k(k + 1)}{2} + k + 1[/tex]
Open the bracket
[tex]d(k) + k + 1 = \frac{k^2 + k}{2} + k + 1[/tex]
Take the LCM
[tex]d(k) + k + 1 = \frac{k^2 + k + 2k + 2}{2}[/tex]
Factorize
[tex]d(k) + k + 1 = \frac{k(k + 1) + 2(k + 1)}{2}[/tex]
Factor out k + 1
[tex]d(k) + k + 1 = \frac{(k + 2)(k + 1)}{2}[/tex]
This gives
[tex]d(k + 1)= \frac{(k + 2)(k + 1)}{2}[/tex]
Because k + 1 satisfies the given function, then the function [tex]d(n) = \frac{n(n + 1)}{2}[/tex] has been proved by induction
Read more about induction at:
https://brainly.com/question/1979616
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.